Small-angle X-ray scattering study of sol-gel-derived siloxane-PEG and siloxane-PPG hybrid materials - Dahmouche, K.; Santilli, Celso Valentim [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Craievich, A. F. (Amer Chemical Soc, 1999)
Hybrid organic-inorganic two-phase nanocomposites of siloxane-poly(ethylene glycol) (SiO3/2-PEG) and siloxane-poly(propylene glycol) (SiO3/2-PPG) have been obtained by the sol-gel process. In these composites, nanometric siloxane heterogeneities are embedded in a polymeric matrix with covalent bonds in the interfaces. The structure of these materials was investigated in samples with different molecular weights of the polymer using the smalt-angle X-ray scattering (SAXS) technique. The SAXS spectra exhibit a well-defined peak that was attributed to the existence of a strong spatial correlation of siloxane clusters. LiClO4-doped siloxane-PEG and siloxane-PPG hybrids, which exhibit good ionic conduction properties, have also been studied as a function of the lithium concentration [O]/[Li], O being the oxygens of ether type. SAXS results allowed us to establish a structural model for these materials for different basic compositions and a varying [Li] content. The conclusion is consistent with that deduced from ionic conductivity measurements that exhibit a maximum for [O]/[Li] =15.